Zasada partnerstwa i jej praktyczne znaczenie w polityce regionalnej na przykładzie Polski - Rudolf, Wawrzyniec (The Partnership Principle and its Practical Importance in the Regional Policy Using the Example of Poland, 2006)
The partnership principle is one of the 4 key rules of the European regional policy and its importance during the following programming periods increases. It emphasizes the need for creating partnership in the regional policy process. The idea of partnership is to integrate different partners around the regional problems. It should result in better development of the region.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 44-53